PRC2, Chromatin Regulation, and Human Disease: Insights From Molecular Structure and Function - Liu, Xiuli; Liu, Xin (Frontiers in Oncology, 2022)
Polycomb repressive complex 2 (PRC2) is a multisubunit histone-modifying enzyme complex that mediates methylation of histone H3 lysine 27 (H3K27). Trimethylated H3K27 (H3K27me3) is an epigenetic hallmark of gene silencing. PRC2 plays a crucial role in a plethora of fundamental biological processes, and PRC2 dysregulation has been repeatedly implicated in cancers and developmental disorders. Here, we review the current knowledge on mechanisms of cellular regulation of PRC2 function, particularly regarding H3K27 methylation and chromatin targeting. PRC2-related disease mechanisms are also discussed. The mode of action of PRC2 in gene regulation is summarized, which includes competition between H3K27 methylation and acetylation, crosstalk with transcription machinery, and formation of high-order chromatin structure. Recent progress in the structural biology of PRC2 is highlighted from the aspects of complex assembly, enzyme catalysis, and chromatin recruitment, which together provide valuable insights into PRC2 function in close-to-atomic detail. Future studies on the molecular function and structure of PRC2 in the context of native chromatin and in the presence of other regulators like RNAs will continue to deepen our understanding of the stability and plasticity of developmental transcriptional programs broadly impacted by PRC2.